The Existence of Basabali Wiki as A Multimodal Learning among Balinese Language Learners in Higher Education - Diari, Komang Puteri Yadnya (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
Advancements in digital technology have provided various opportunities for integrating innovative platforms like BASAbali Wiki into language learning, particularly in higher education."This present study aimed to discover the existence of BASAbali Wiki among Balinese Language learners in higher education as a tool or platform for multi-modal learning. The study was designed as a qualitative study. It observed a phenomenon in depth. A purposive sampling technique was used to select the study subjects based on criteria. Fifteen students from different universities participated in this study. This study had three instruments: researcher, interview guide, and questionnaire. The preliminary observation used the questionnaire to see the trend of Basabali Wiki. In addition, the data from the interview guide were the primary data in this study. After obtaining the data, it was analyzed qualitatively following data reduction, data display, and conclusion. The study results showed that Basabali Wiki is an effective platform for multimodal learning, which can be used as a learning media, learning source, and dictionary. In addition, students can access it online. Further study on quantitative research is needed to see the effectiveness of its implementation in teaching and learning.